2011
DOI: 10.1167/iovs.11-7613
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Vision- and Health-Related Quality of Life in Patients with Diabetic Macular Edema Treated with Pegaptanib Sodium or Sham

Abstract: PURPOSE. To compare vision function and self-reported quality of life (QoL) in patients with diabetic macular edema (DME) treated with intravitreous pegaptanib 0.3 mg or sham injection. METHODS. This randomized (1:1), controlled, multicenter trial included subjects with DME (center point thickness on OCT, Ն250 m) and visual acuity (VA) Յ65 letters and Ն35 letters. In year 1, pegaptanib or sham was administered every 6 weeks with focal/grid photocoagulation at investigator discretion after week 18. Subjects rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 29 publications
(24 reference statements)
3
14
0
Order By: Relevance
“…These outcomes were similar, but of greater magnitude, to an analysis of randomized controlled trial data for pegaptanib treatment. 18 In the RESTORE trial, approximately half of the patients achieved at least a 5-point improvement in the NEI VFQ-25 composite score with ranibizumab monotherapy and 43% with ranibizumab plus laser at the 12-month follow-up visit compared with 31% with laser alone. Greater improvements from baseline for ranibizumab monotherapy compared with laser alone were also noted on the subscales for near activities (visual activities, including reading ordinary print in a newspaper and close-up work or hobbies, such as cooking or using hand tools) and general vision (perception of how good their eyesight is).…”
Section: Discussionmentioning
confidence: 99%
“…These outcomes were similar, but of greater magnitude, to an analysis of randomized controlled trial data for pegaptanib treatment. 18 In the RESTORE trial, approximately half of the patients achieved at least a 5-point improvement in the NEI VFQ-25 composite score with ranibizumab monotherapy and 43% with ranibizumab plus laser at the 12-month follow-up visit compared with 31% with laser alone. Greater improvements from baseline for ranibizumab monotherapy compared with laser alone were also noted on the subscales for near activities (visual activities, including reading ordinary print in a newspaper and close-up work or hobbies, such as cooking or using hand tools) and general vision (perception of how good their eyesight is).…”
Section: Discussionmentioning
confidence: 99%
“…There are several therapeutic modalities for DME, such as focal laser photocoagulation, intravitreal or subtenon's injection of triamcinolone acetonide, intravitreal bevacizumab, and pars plana vitrectomy (Bressler et al, 2014;Hariprasad et al, 2008;Loftus et al, 2011;Nguyen et al, 2010;Okamoto et al, 2014). The Early Treatment for Diabetic Retinopathy Study (ETDRS) has reported the beneficial effect of laser photocoagulation for patients with clinically significant macular edema (CSME) (Brown et al, 2013;Tranos et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…A trial reported in 2011 showed administration of intravitreal pegaptanib every 6 weeks for 1 year resulted in statistically significant improvement compared to sham in both visual acuity as measured by ‡10-letter gains (p = 0.0047) and patient quality of life as measured by a >5-point difference in the National Eye Institute Visual Functioning Questionnaire 25 [59].…”
Section: Anti-vegf Agentsmentioning
confidence: 99%